FROM ‘HYPHENATED CATHOLICS’ TO THE CHURCH ‘CATHOLIC’: PILGRIMAGE OF HUMILITY AND HOPE INTO ‘COMMUNION’ OF LOVE AND TRUST - Karekatt, Raphael (Asian Horizons, 2014)
There was a great deal of trepidation, uncertainty and anxiety in the church as the 50th year of Vatican II drew near, especially with regard to the future and destiny of the discernments of the council and the reform it had inaugurated. But as it has happened in the ages past, God appears to have decisively stepped in to light the way forward, pointing the directions the journey must go. The election of Francis as the Pope and the subsequent events that have followed have already profoundly transformed the church and her self-understanding, generating a new atmosphere of openness, courage, hope and trust. The following reflection scans the contemporary ecclesial landscape to examine how this new hopeful atmosphere will impact the reform in general and the perennial quest to recover and grow in the ‘communion’ that marks the ‘Church Catholic’, learning in the process to hold in creative tension all the diversity that characterizes this communion.